Pengembangan Aplikasi Inshot Sebagai Media Pembelajaran Kreatif - Alya Mulyani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Currently there are many learning media that can be used by teachers to support teaching and learning activities with students. The more the times, the more modern the technology that exists today. An example of an item that we often use in our daily lives is gadgets. Various applications are offered on both android and IOS-based devices. For example applicationinshot which is used to create or edit simple videos easily. This research uses a method with a qualitative approach. The problem in this research is how to develop applicationsinshot as a creative learning media. The purpose of this research is to develop applicationsinshot as a creative learning medium that can be used in a variety of subjects at the primary and secondary education levels. The result of this research is applicationinshot really helps teachers in making creative learning media.Â